THE ROLE OF AFFERENT LYMPHATICS IN THE REJECTION OF SKIN HOMOGRAFTS - Barker, Clyde F. (The Rockefeller University Press, 1968)
Experiments have been carried out on guinea pigs of two isogenic strains to elucidate the role of afferent lymphatic vessels in the rejection of orthotopic skin homografts. Graft beds were prepared in partially isolated skin flaps with an intact sustaining vascular "umbilical cord" in which a lymphatic connection with the host could be retained or abolished at will. In the absence of demonstrable lymphatic connections between flap and host, intra-flap homografts long outlived similar grafts transplanted to conventional sites in intact skin and, rather than being specifically rejected, died as a consequence of ischemic necrosis of the flap. When lymphatic drainage was retained, intra-flap homografts were rejected in the usual manner. Hosts of long-term intra-flap homografts did not develop sensitivity, as evidenced by the "first set" type rejection of subsequent test grafts, or by the long-term survival of a second skin graft transplanted to a new flap raised on the opposite side of the host's body. Intra-flap skin homografts were rejected if (a) the hosts had been presensitized, (b) they were grafted concomitantly with a skin homograft placed in a conventional site, or inoculated with a suspension of donor lymphoid cells, or (c) if the lymphatic drainage was restored by reimplantation of the hitherto partially isolated flap to an appropriate vascular bed. These findings and others indicate that an intact lymphatic drainage in its bed is essential for an orthotopic skin homograft to sensitize its host. Various experiments were carried out in which intra-flap homografts were used as "indicators" for the acquisition of specific active or adoptive immunity by their hosts. By transplanting skin homografts to conventional beds concomitantly with intra-flap grafts and then excising the former at various intervals, it has been found that a graft must be in residence for a minimum period of 4 days to evoke the development of a detectable level of sensitivity in the host. Furthermore, by replacing either freshly prepared or long-term skin flaps bearing skin homografts in vascular beds on the trunk and determining the subsequent survival times of the homografts, evidence has been obtained suggesting that reestablishment of a functional lymphatic system in a free skin graft may take as long as 9 days. Using intra-flap homografts as indicators of adoptive immunization of the host, we found that as few as 50 x 10(6) isologous peripheral blood leukocytes from a specifically sensitized animal will transfer an effective level of sensitivity. We also found that hyperimmune serum, in relatively large amount, exerts a weak but definite adverse effect upon either freshly or recently transplanted intra-flap grafts.